In situ synthesis of GeO2/reduced graphene oxide composite on Ni foam substrate as a binder-free anode for high-capacity lithium-ion batteries. Issue 4 (4th December 2014) - Qiu, Heyuan; Zeng, Lingxing; Lan, Tongbin; Ding, Xiaokun; Wei, Mingdeng
Abstract : The GeO2 /RGO electrode is successfully fabricated via a facile dip-coating route cooperated with in situ hydrolysis of GeCl4 and used directly as a binder-free anode for LIBs. This material exhibited high reversible capacity, good cycling performance and excellent rate capability. Abstract : A GeO2 /RGO composite was successfully fabricated via alternating deposition of graphene oxide (GO) and GeO2 on the surface of a Ni foam substrate using a facile dip-coating method cooperated with in situ hydrolysis of GeCl4 . This material was directly used as a binder-free anode for LIBs and exhibited high reversible capacity (1716 mA h g −1 at 0.2 A g −1, 702 mA h g −1 at 16 A g −1 ), good cycling performance (1159 mA h g −1 at 1 A g −1 after 500 cycles) and excellent rate capability. In addition, a reversible capacity as high as 621 mA h g −1 can be retained when cycled to 500 cycles at a rate as high as 8 A g −1 .